Congenital Absence of pericardium - Sharma, D; Baidya, SG; Prajapati, D; Lamsal, K; Kayastha, B; Pant, S; Ghimire, RK (Nepalese Heart Journal, 2013)
A 30- year-old physically active male presented to us for evaluation of left sided chest pain which was non-exertional in nature. He described it as being of pricking type and non-radiating .His past history was not significant. Physical examination revealed a non-palpable apical impulse with no other abnormal findings. A chest x-ray (P-A view) revealed levoposition of heart, loss of the right heart border (hidden by spine) and prominence of pulmonary artery segments(Fig 1).A “tongue” of lung interposing between aorta and pulmonary artery was not evident in chest x-ray in this case. ECG was taken in the supine position with precordial leads placed in the standard position , which revealed right axis deviation, right bundle branch block(RBBB) pattern and poor R wave progression(Fig2). Transthoracic echocardiography revealed unusual windows with marked lateral displacement of apical windows. Lateral placement of the transducer was also necessary for parasternal axis views. Right atrium and right ventricles were mildly dilated. Echocardiography excluded other structural heart diseases (Fig 3 and Fig 4). As the above findings were suggestive of the diagnosis of congenital absence of pericardium, further investigations including CT chest and cardiac MRI were done to confirm the diagnosis. CT thorax(Fig 5), also suggested absence of pericardium. Axial T1 weighted cardiac MRI revealed markedly rotated axis of the the heart with mildy dilatation of ventricles. Lung was seen insinuating between aorta and pulmonary artery. Pericardium was absent(Fig 6). Thus, the diagnosis of total absence of pericardium was confirmed. Patient was advised to continue activities without limitation and was not referred for any kind of intervention. DOI: http://dx.doi.org/10.3126/njh.v9i1.8350 Nepalese Heart Journal Vol.9(1) 2012 pp.53-55